Mathematical Thinking Assessment (Mata) Framework: A Complete Guide - Hwa , Tee Yong (2010)
The main purposes of this study were to develop a Mathematical Thinking Assessment (MaTA) Framework and to examine its usability and practicality. The MaTA Framework consists of four major components: Performance Assessment; Metacognition Rating Scale; Mathematical Disposition Rating Scale; and Mathematical Thinking Scoring Rubric. It provides a comprehensive guideline for secondary school mathematics teachers in assessing students’ mathematical thinking. This study was undertaken in two phases. The developmental phase involved 5 mathematics experts, 34 secondary school mathematics teacher and 188 Form Four students. The completed MaTA Framework developed in the developmental phase was then piloted in four secondary schools by 6 school mathematics teachers and 203 Form Four students in their respective classes. Qualitative data were collected through structured interviews with mathematics experts and secondary school mathematics teachers, focus group interview, written feedback in workshops, teacher reflection journals and students’ written solutions. As for quantitative data, two sets of questionnaires were administered to the participating teachers and students respectively with the aim of eliciting their views on the usability and practicality of implementing the MaTA Framework in the school context.